Pengetahuan dan Sikap Keuangan: Perspektif Manajemen Keuangan dan Financial Self-Eficacy di Lingkungan Desa - Rosyidah, Ulifatur; Santoso, Rahmat Agus (Magister Akuntansi Universitas Pancasila, 2024)
This research was conducted to determine the factors that influence the Financial Management Behavior of Women Empowering Family Welfare in Sukomulyo Village. This research aims to analyze the influence of Financial Knowledge and Financial Attitude variables on Financial Management Behavior with Financial Self-efficacy as a mediating variable among Mothers who are Family Welfare Empowerment (PKK) Administrators in Sukomulyo Village, Manyar District, Gresik Regency. The type of research used is quantitative with data analysis techniques using PLS (Partial Least Square) analysis with the SmartPLS program. The population and sample used in this research were the Family Welfare Empowerment (PKK) administrators at the Sukomulyo Village Community Association, totaling 135 respondents. The research results show that Financial Knowledge and Financial Attitudes have a positive effect on Financial Management Behavior. Apart from that, both also have a positive effect on Financial Self-efficacy, which in turn also influences Financial Management Behavior. Financial Self-efficacy also functions as a mediating variable, which connects Financial Knowledge and Financial Attitudes with Financial Management Behavior. These findings emphasize the importance of having good Financial Knowledge, a positive Financial Attitude, and strong Financial Self-efficacy in forming wise financial management behavior among mothers in the village.